2018
DOI: 10.1002/jcb.27974
|View full text |Cite
|
Sign up to set email alerts
|

Dual actions of the antioxidant chlorophyllin, a glutathione transferase P1‐1 inhibitor, in tumorigenesis and tumor progression

Abstract: Glutathione (GSH) and enzymes related to this antioxidant molecule are often overexpressed in tumor cells and may contribute to drug resistance. Blockade of glutathione transferases (GSTs) has been proposed to potentiate the efficacy of chemotherapeutic drugs in cancer. The aim of this study was to evaluate the effect of chlorophyllin that has antioxidant properties, and also interferes with the activity of GST P1‐1, on breast cancers in vitro and in vivo. The in vivo studies were conducted using an N‐methyl‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Chlorophyllin enhanced the nuclear translocation of Nrf-2 in mouse splenic lymphocytes in both a dose- and time-dependent manner [ 201 ]. In rats with breast cancer, chlorophyllin increased the GSH levels in the liver [ 202 ].…”
Section: Antioxidant Capacity Of Chlorophyllsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorophyllin enhanced the nuclear translocation of Nrf-2 in mouse splenic lymphocytes in both a dose- and time-dependent manner [ 201 ]. In rats with breast cancer, chlorophyllin increased the GSH levels in the liver [ 202 ].…”
Section: Antioxidant Capacity Of Chlorophyllsmentioning
confidence: 99%
“…Chlorophyllin enhanced the nuclear translocation of Nrf-2 in mouse splenic lymphocytes in both a dose-and time-dependent manner [201]. In rats with breast cancer, chlorophyllin increased the GSH levels in the liver [202]. Another line of research comes from the assumption that chlorophyll a and its derivatives have been proposed to exert antidiabetic functions [203].…”
Section: In Vivo Activation Of Detoxification Pathways By Chlorophyllsmentioning
confidence: 99%
“…For instance, the activation of signaling pathways containing TGFβ, WNT, NOTCH, MYC, and EMT-related genes occur only late during hepatocarcinogenesis and they affect oncogenic driver genes for cell survival, angiogenesis, and treatment resistance. [38][39][40]…”
Section: Potential Therapies Through Targeting Driver Genes and Key Pathwaysmentioning
confidence: 99%
“…Chlorophyllin was shown to be a speci c inhibitor of GSTP1. In a previous study of our group, it was demonstrated that chlorophyllin had a suppressing effect on the spread of breast cancer in an animal model chemically induced with N-methyl nitrosourea (Ozcan, Esendagli et al 2018). However, in this study, the e cacy of chlorophyllin administration on breast cancer-induced liver metastasis was investigated, and it was revealed that chlorophyllin might have inhibitory effects on metastasis by reducing migration, MMP expression, and enzyme activity.…”
Section: Discussionmentioning
confidence: 80%